2023
DOI: 10.3389/fneur.2023.1086465
|View full text |Cite
|
Sign up to set email alerts
|

Role of plaque inflammation in symptomatic carotid stenosis

Abstract: ObjectivePrior studies have shown that plaque inflammation on FDG-PET and the symptomatic carotid atheroma inflammation lumen-stenosis (SCAIL) score were associated with recurrent ischemic events, but the findings have thus far not been widely validated. Therefore, we aimed to validate the findings of prior studies.MethodsA single-center prospective cohort study that recruited patients with (1) recent TIA or ischemic stroke within the past 30 days, (2) ipsilateral carotid artery stenosis of ≥50%, and (3) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Per g/mL increase in SUV max there was an approximate twofold increased risk of early recurrent stroke (HR 2.19, 95% CI, 1.41-3.39; p < 0.001) [74]. These findings have since been replicated in another study performed in Singapore with similar eligibility criteria [75]. More recent work demonstrated that FDG uptake in the SHS is also associated with 5-year ipsilateral stroke recurrence even after accounting for carotid revascularization and stenosis severity (HR 1.98, 95% CI 1.10-3.56, p = 0.02, per g/mL) [76].…”
Section: Carotid Plaque Inflammation and Stroke Riskmentioning
confidence: 63%
“…Per g/mL increase in SUV max there was an approximate twofold increased risk of early recurrent stroke (HR 2.19, 95% CI, 1.41-3.39; p < 0.001) [74]. These findings have since been replicated in another study performed in Singapore with similar eligibility criteria [75]. More recent work demonstrated that FDG uptake in the SHS is also associated with 5-year ipsilateral stroke recurrence even after accounting for carotid revascularization and stenosis severity (HR 1.98, 95% CI 1.10-3.56, p = 0.02, per g/mL) [76].…”
Section: Carotid Plaque Inflammation and Stroke Riskmentioning
confidence: 63%